Molecular Microbial Diagnostic Methods pathways to implementation for the food and water industries - Cook, Nigel; Ed. ; Thompson, K.C; Ed (Academic Press is an imprint of Elsevier, 2016)
Molecular Microbial Diagnostic Methods: Pathways to Implementation in the Food and Water Industries attempts to address the shortage of guidance on implementation of molecular-based methods for routine diagnostic laboratories. What industry and analysts can expect from routine use of these methods is discussed and outlined. The book uncovers industry needs for the use of molecular methods by providing a brief history of water and food analysis for the pathogens of concern. It also describes the potential impact of current and cutting-edge molecular methods. It discusses the advantages of the implementation of molecular methods, describes information on when and how to use specific methods, and presents why one should utilize them for pathogen detection in the routine laboratory. The reference material in the book is also pertinent for anyone carrying out microbiological analysis at the research level and covers a wide spectrum of classical and cutting-edge methods.